Penerapan Parate Eksekusi Atas Hak Tanggungan Oleh Perusahaan Modal Ventura - Helmi Akbar Jungjunan; Fauzie Yusuf Hasibuan (Postgraduate of Jayabaya University, 2016)
The purpose of this research is the Parate Executie of the Court of First Instance and/or Private Sales, the one of business activities of a Venture Capital Company (PMV) is financing/capital participation in an Investee Company for a certain period of time based on the profit sharing agreement. This research using a normative juridical legal research conducted as an effort to obtain the necessary data with respect to the problem. The data used are secondary data consisting of primary legal materials, secondary legal material, and tertiary legal materials. The primary data are also used to support secondary data. The data analysis was conducted using qualitative normative analysis. The research results it was concluded that the implementation of the settlement of non-performing finance can be done through Parate Executie in a manner as referred to in A). Article 20 paragraph (1) letter “a” in conjunction with Article 6 in conjunction with; B). Article 14 paragraph (2) in conjunction with Article 20 paragraph (1) and/or C). Article 20 paragraph (2) of Law on Mortgage Rights, that is selling the mortgage rights object on its own authority through a public auction according to the procedures as specified in the laws and regulations; and the petition for Fiat Executie by a Court of First Instance for the execution of mortgage rights is based on title executorial; and the settlement of non-performing finance is through the Private Sales against the collateral that has been tied by Mortgage Rights.